A temporally dynamic Foxp3 autoregulatory transcriptional circuit controls the effector Treg programme - Bending,D; Paduraru,A; Ducker,C; Prieto,Martin P; Crompton,T; Ono,M (The EMBO Journal, 2018)
Regulatory T cells (Treg) are negative regulators of the immune response; however, it is poorly understood whether and how Foxp3 transcription is induced and regulated in the periphery during Tcell responses. Using Foxp3Timer of cell kinetics and activity (Tocky) mice, which report realtime Foxp3 expression, we show that the flux of new Foxp3 expressors and the rate of Foxp3 transcription are increased during inflammation. These persistent dynamics of Foxp3 transcription determine the effector Treg programme and are dependent on a Foxp3 autoregulatory transcriptional circuit. Persistent Foxp3 transcriptional activity controls the expression of coinhibitory molecules, including CTLA4 and effector Treg signature genes. Using RNAseq, we identify two groups of surface proteins based on their relationship to the temporal dynamics of Foxp3 transcription, and we show proof of principle for the manipulation of Foxp3 dynamics by immunotherapy: new Foxp3 flux is promoted by antiTNFRII antibody, and highfrequency Foxp3 expressors are targeted by antiOX40 antibody. Collectively, our study dissects timedependent mechanisms behind Foxp3driven Tcell regulation and establishes the Foxp3Tocky system as a tool to investigate the mechanisms behind Tcell immunotherapies.